2018
DOI: 10.1177/0022034518756889
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin Is Required for Alveolar Bone Homeostasis

Abstract: Tristetraprolin (TTP) is an RNA-binding protein that targets numerous immunomodulatory mRNA transcripts for degradation. Many TTP targets are key players in the pathogenesis of periodontal bone loss, including tumor necrosis factor-α. To better understand the extent that host immune factors play during periodontal bone loss, we assessed alveolar bone levels, inflammation and osteoclast activity in periodontal tissues, and immune response in draining cervical lymph nodes in TTP-deficient and wild-type (WT) mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 33 publications
(45 reference statements)
1
31
0
Order By: Relevance
“…These images were rotated with a standard orientation and threshold to discern mineralized and non‐mineralized tissue. The region of interest (ROI) was indicated by the contour height of molars (M1‐M3) at the cementoenamel junction as the width and the molar cusp tips to root apices as the height as recently reported . Depth was equal to the buccolingual size of the teeth plus 1.0 mm 3 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These images were rotated with a standard orientation and threshold to discern mineralized and non‐mineralized tissue. The region of interest (ROI) was indicated by the contour height of molars (M1‐M3) at the cementoenamel junction as the width and the molar cusp tips to root apices as the height as recently reported . Depth was equal to the buccolingual size of the teeth plus 1.0 mm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…The region of interest (ROI) was indicated by the contour height of molars (M1-M3) at the cementoenamel junction as the width and the molar cusp tips to root apices as the height as recently reported. 26 Depth was equal to the buccolingual size of the teeth plus 1.0 mm 3 . Bone volume fraction was calculated as the percentage of bone within the ROI using AnalyzePro software (Seattle, WA).…”
Section: Alveolar Bone Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Besides MDSCs being macrophage progenitors, which can also become osteoclasts, we and others have suggested that MDSCs may directly become osteoclasts in the right bone microenvironment-either in the context of aging or cancer (Sawant and Ponnazhagan 2013;Steinkamp HM 2018). Indeed, we show in Figure 3, that MDSCs or circulating monocytes (CD11b + LY6G − LY6C high ) isolated from 12-week-old mice can differentiate directly into osteoclasts in response to RANKL/M-CSF.…”
Section: Mdsc Expansion Osteoclastogenesis and Oxidative Stressmentioning
confidence: 63%
“…Likewise, it is not known of the same mechanisms of MDSC differentiation into osteoclasts are operative compared to other osteoclastogenic populations. However, our group has recently shown that mice deficient in the RNA binding protein, tristetraprolin, where there is significant amounts of TNF-α being expressed, have an increased expansion of MDSC population and increased bone loss in the alveolar bone (Steinkamp HM 2018). Ongoing studies are addressing the potential mechanisms.…”
Section: Mdsc Expansion Osteoclastogenesis and Oxidative Stressmentioning
confidence: 99%